In vitro study of antioxidant and antimicrobial activities of soybean tempeh and split gill fungus (Schizophyllum commune) as plant-based diets - Yodsenee, K.; Suthirawut, S.; Pilasombut, K.; Urairong, H.; Rumjuankiat, K. (My University, 2022)
Plant-based diets that reduce or eliminate animal product intake are known to ameliorate the incidence and clinical course of several illnesses. Soybean tempeh and split gill edible fungus (Schizophyllum commune) have long been consumed as plant-based diet choices. Total phenolic content (TPC), antioxidant and antimicrobial activities of soybean tempeh and S. commune extracts were investigated using water for extraction. The aqueous extract of fresh S. commune had the highest TPC at 1191.81 mg GAE/100g. Three methods were evaluated antioxidant activity as the diphenyl picrylhydrazyl radical scavenging test (DPPH), radical cation decolorization assay (ABTS) and reducing power. The IC50 values of fresh S. commune using DPPH and ABTS+ assays were 0.2812% and 0.5761%, respectively whereas the reducing power assay gave EC50 value at 0.3606%. Crude extracts of fresh tempeh and fresh S. commune exhibited antimicrobial activity against Staphylococcus aureus TISTR 746 at concentrations of 25 and 50 mg/ml, respectively. Two times the minimum inhibitory concentration (MIC) of fresh tempeh and fresh S. commune effectively reduced viable cells of S. aureus TISTR 746 of 5 log CFU/ml at 12 h. Both fresh tempeh and S. commune extracts showed promise as natural antioxidants for utilization as plant-based food.
Keywords: Antimicrobial activity; Antioxidant; Plant-based diet; Schizophyllum commune; Soybean tempeh